Synergies and trade-offs in the management objectives forest health and flood risk reduction - Rackelmann, Fabian; Sebesvari, Zita; Bell, Rainer (Frontiers in Forests and Global Change, 2023)
While healthy forest ecosystems deliver various services that can reduce flood risk, they can also contribute to flooding by providing wood that potentially contributes to the clogging of waterways and associated backwater effects. In this regard, deadwood, as a key aspect of healthy forests, is often in focus of post-flood disaster discourses. This research reflects on this ambiguity in the different forest management goals when it comes to managing forests for flood risk reduction versus forest health. A working definition of forest health will be presented and an overview of the different aspects of how a forest potentially can affect the flood hazard will be provided. This will refer to the ways forests influence (1) the discharge of water from the landscape into channels and (2) the characteristics of the channel and its riparian area and their respective influence on the transport of water, sediment, and debris. Often these two determining factors for the development of the flood peak are discussed separately and by different academic fields. This paper aims to connect the existing knowledge spheres and discusses the synergies and trade-offs. The review shows that the two objectives of forest health and flood risk reduction are largely synergetic. However, in direct proximity to watercourses trade-offs might occur. This is especially due to the ambivalent relation of living vegetation and deadwood to flood hazard. In places without susceptible infrastructures to clogging, deadwood and diverse vegetation structures should be supported due to their beneficial effects on water retention and channel characteristics. In places where susceptible infrastructures exist, trade-offs between the two objectives arise. Here the potential of freshly uprooted vegetation to cause damages should be reduced while maintaining the vegetation's supportive characteristics, for example, concerning bank and slope stability. Where the risk of clogging is assessed as too high, also the selective removal or shortening of dead in-channel Large Wood can be considered. However, based on the literature review the risk deriving from dead Large Wood is evaluated as comparably low. This is related to its generally lower proportions and its smaller and less stable characteristics compared to freshly uprooted vegetation.